Minimal incision surgery in hallux rigidus - de Prado, Mariano; Cuervas-Mons, Manuel (Journal of the Foot & Ankle, 2022)
The choice of surgical technique in the treatment of hallux rigidus is an individual decision of the surgeon. Minimally invasive osteotomies have proven to be valid techniques, allowing us to perform cheilectomies, first proximal phalangeal osteotomies, and distal first metatarsal osteotomies. We describe the minimally invasive technique for the treatment of hallux rigidus. Level of Evidence V; Therapeutic Study; Expert opinion.